The Effectiveness of Quizlet-Based Guided Discovery Learning on Vocabulary Mastery at a Junior High School in Pematangsiantar - Clara, Elisabeth Dwi; Napitupulu, Selviana (Journal of English Language Teaching and English Linguistics, 2026)
In many Indonesian junior high schools, students often struggle to retain English vocabulary due to the dominance of passive, teacher-centered memorization techniques. Although digital tools are readily available, their systematic integration with structured pedagogical frameworks, such as Guided Discovery Learning (GDL), remains scarce in local EFL contexts. Addressing this gap, this study evaluates the efficacy of integrating GDL with Quizlet to improve the vocabulary mastery of eighth-grade students at SMP Negeri 10 Pematangsiantar. The research employed a quantitative quasi-experimental design with 60 students selected via purposive sampling. The experimental group was taught using the GDL-Quizlet model, while the control group followed conventional instruction. Data analysis using non-parametric statistics revealed that the experimental group significantly surpassed the control group. While the control group showed stagnant results, the experimental group demonstrated substantial gains. These findings suggest that combining the scaffolding of GDL with the gamified engagement of Quizlet creates a highly effective learning environment, offering a practical solution for teachers aiming to boost student motivation and lexical competence. Keywords: EFL Students, Guided Discovery Learning, Quizlet, Vocabulary Mastery, Quasi-Experimental Research